Development of Gatra Trigger National Resilience in Combating the Threat of Foreign Intelligence Covert Actions - Pujo Widodo; Moh Khusaini; Alfi Haris Wanto; Panji Suwarno; Vasyl Maliyk (Nusantara: Journal of Law Studies, 2026)
Developments in the global strategic environment indicate that threats to the state are no longer limited to conventional military conflicts but also encompass non-conventional threats, such as covert actions conducted by foreign intelligence agencies to influence a country's political, social, economic, and security stability. In this context, strengthening national resilience becomes a strategic instrument for identifying, anticipating, and addressing hidden and multidimensional threats. The analytical framework of national resilience in Indonesia employs the Astagatra approach, which consists of Trigatra (geography, natural resources, and demography) and Pancagatra (ideology, politics, economy, socio-culture, and defense and security) as the core elements shaping national resilience against various strategic threats. This research adopts a qualitative approach with a case study design. The findings reveal that the development of "gatra triggers" can strengthen the national early warning system by integrating counter-intelligence indicators, including prevention, detection, strategic deception, neutralization, counterespionage, and security measures across all aspects of Astagatra. This approach enables the identification of vulnerabilities in geography, natural resources, demography, ideology, politics, economy, socio-culture, and defense and security that foreign intelligence actors may exploit in conducting covert influence operations. At the same time, it enhances synergy among state institutions and strengthens the capacity of early detection systems in safeguarding national stability and interests. The academic contribution of this study lies in developing the "gatra trigger" concept as an integrated framework that bridges national resilience and counterintelligence studies, thereby reinforcing early warning systems and adaptive national security policies against covert foreign influence operations.